(untitled) (Academia Journal of Medicine, 2017)
Background: Dengue Fever which is also known as break bone fever is a benign syndrome begin by many arthropod– borne viruses, which is specify by myalgia, high grade fever, or arthralgia, rash, leukopenia and lymphadenopathy. Our study was carried out with an aim to describe the different clinical spectrums of dengue with its hematological profile. Subjects and Methods: A total of 130 cases were anticipated with age of all groups, and those who were serologically positive for Dengue tested by ELISA/Card (NS1, IgG, IgM) method were included in this study. Patients found to be serologically dengue negative and positive patients who were also found to be positive for other coexisting infections, viz. malaria, typhoid, etc and not done the clinical test were excluded, so this study included all patients diagnosed with dengue. The examination based on WHO criteria and the case definition was based on compatible clinical history and, confirmed by positive serology for dengue applying the ELISA IgM method. All patients with bleeding manifestations, thrombocytopenia with platelet count < 30,000 cu/mm were admitted and pregnant patients and infants with decrees platelet counts were admitted. Results: Out of a total of 130 cases enrolled in the study a total of 75 (58%) did not have bleeding manifestations and comprised the Group I of study where as remaining 55(42%)patients presented with bleeding manifestations and were placed in Group II of study. Among these 130 patients with confirmed diagnosis, 75were Group I while the rest were Group II giving a Group I to Group II. Their ages ranged from 4 years to 80 years. Conclusion: In the current study the clinical profile of patients having bleeding manifestations which is the extreme form of dengue fever was marked by raised portion of hepatomegaly and decreased platelet count. The clinical course of disease is marked by a rationalization of platelet count by day 5 of illness. Dengue fever does not have specific medical therapy hence clinical recovery monitoring is largely dependent on haematological parameters. This study concludes that parameter like platelet count, haematocrit, leukocyte count and coagulation studies aid greatly in clinical monitoring of patient.